Virtual Reality Body Image Training for Chronic Low Back Pain: A Single Case Report - Harvie, Daniel S.; Rio, Ebonie; Smith, Ross T.; Olthof, Nick; Coppieters, Michel W. (Frontiers in Virtual Reality, 2020)
Background: Virtual reality (VR) allows people to embody avatars that are different from themselves in appearance and ability. These experiences provide opportunities to challenge bodily perceptions. We devised a novel VR Body Image Training (VR-BIT) approach to target self-perceptions and pain in people with persistent pain. Methods: A 45-year old male with a 5-year history of disabling chronic low back pain participated in a four week VR-BIT intervention. Pain began following a fall from a first-floor deck. Pain was central and on the right side of his lower back, radiating to his right buttock and thigh. Pain was constant and varying at a 5/10 average intensity. The 4-week intervention consistent of three face-to-face sessions one week apart, followed by 1-week of in-home VR-BIT. During the first face-to-face session, the participant embodied three athletic avatars: a superhero (Incredible Hulk), a boxer, and a rock climber. Since the participant strongly identified with the boxer, only boxing experiences were subsequently used. Primary outcomes relating to body image (self-perceived strength, vulnerability, agility and confidence with activity) and pain intensity were assessed using numerical rating scales (0 to 10 NRS). Disabilility, kinesiophobia, overall change, and self-efficacy were assessed as secondary outcomes. Outcomes were assessed during each face-to-face session, and at 1-week and 3-month follow-up. Results: The participant reported a high degree of engagement. Positive changes were noted during and after VR for all body image and pain assessments. Improvements were retained at 3-months for body image ratings (mean change: 4.5/10 NRS) and average pain intensity (change: 2/10 NRS)). Improvements in disability (45% improvement); self-efficacy (pre: 2/12; post: 10/12); and overall change (‘Very much improved’) were noted at 3-month follow-up. No change in kinesiophobia was detected. No adverse advents were recorded. Conclusion: The participant engaged strongly with the intervention and showed clinically meaningful changes in body image, pain, disability and self-efficacy. Despite his long history of pain and rapid improvements, reported changes may be due to non-treatment effects. Nonetheless, VR-BIT clearly warrants further investigation as a potential addition to usual care.